Akame ga kill!. 2 - Takahiro, 1981- (Yen Press, Hachette Book Group, 2015)
"Now a member of the assassination squad Night Raid, Tatsumi must soon face an enemy equipped with a Teigu. These ancient super-weapons are so mighty that when two opponents wielding Teigus battle, one is guaranteed to die..."--Publisher's website.